Follicular and luteal progesterone synergize to maintain 5-day cyclicity in rats. (Revista Española de Fisiología, 1996)
The length of the ovarian cycle in rat is determined by the duration of progesterone secretion from the corpora lutea (CL) during diestrus. The action of progesterone secretion from the preovulatory follicles on proestrus is also responsible for the cycle length in 4-day cyclic rats. To study whether follicular and luteal progesterone participate in the maintenance of 5-day cyclicity, the effects of the antiprogestagen RU486 (5 mg on proestrus or estrus) on estrous cycle length and on the serum concentrations of LH in 5-day cyclic rats and in 4-day cycle experimentally induced by the dopamine agonist CB154 (1 mg on estrus) were investigated. Furthermore, serum concentrations of progesterone on the day of ensuing ovulation were measured to see whether activation of the CL function after treatment with RU486 had occurred. Both 5-day and CB154-injected rats had a 3-day estrous cycle after RU486 on proestrus, while RU486 on estrus shortened by 1-day the estrous cycle length in 5-day but not in CB154-injected rats. Basal serum concentrations of LH increased and the LH surge decreased after RU486 treatment in both cycle types. Serum concentrations of progesterone rose only in 5-day rats injected with RU486. These results indicate that the actions of both follicular and luteal progesterone synergize in maintaining the length of the estrous cycle in 5-day cyclic rats and that functionally active CL increase progesterone production only under the action of a complete surge of prolactin.